Pedagogical Leadership, Teaching Leadership and their Role in School Improvement: A Theoretical Approach - Contreras, Trilce S. (2016)
Educational demands of the 21st century make it indispensable to re-evaluate the traditional models of management and leadership in schools and focus on pedagogical aspects, distributed leadership, participative school development and teachers’ professional growth. Pedagogical leadership includes these aspects and it is emerging, within the educational research field, as the most effective model to achieve sustained improvements in the schools. Teaching leadership is an essential element of this model and it has also been accredited, in recent years, as a fundamental characteristic of a successful school. A theoretical-conceptual approach of pedagogical and teaching leadership is made, presenting the conditions in which they can be developed, and their role in school improvement. Conclusions are the following: Teachers, their leadership potential and pedagogical leadership, define a new comprehensive notion of school which is aimed to serve the students and their learning process, and to promote human and professional development. In order to achieve an educational change and school development, it is essential that teachers and principals are appropriately trained and empowered, and become aware of their key role within such processes.